Implementasi Penilaian Autentik Bahasa Indonesia Bermuatan Literasi Digital-Industri di SMK dalam Paradigma Kebijakan Edukasi 5.0 - Fadilla, Annisa Rizky; Suhardi, Suhardi; Sudiati, Sudiati (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The 5.0 education policy reflected through the Merdeka Curriculum directs to a meaningful reality that is truly applicable and functional. This study aims to describe the implementation of an authentic assessment of Indonesian Language subjects which includes digital-industry literacies at SMK Muhammadiyah 2 Muntilan. The research uses a descriptive method with a qualitative approach. Sources of data to answer research questions are the results of interviews (teachers and students) and the analysis of learning documents. The data collection method uses basic direct talk techniques and advanced techniques such as recording and taking notes. Data validity was tested using referential validity, while reliability was tested using intra-rater and inter-rater techniques. The results of the analysis show that SMK Muhammadiyah 2 Muntilan has implemented various forms of authentic assessment of Indonesian Language subjects in the Industrial Learning (PI) program which also includes ocationally-appropriate digital-industry literacies. Implementing the Indonesian Language authentic assessment with digital-industry literacies at SMK Muhammadiyah 2 Muntilan is considered good because it fulfills the performance and meaningful aspects to support students' Indonesian language skills according to the 5.0 education policy.